Draft Genome Sequences of Pandrug-Resistant Serratia marcescens Clinical Isolates Harboring bla NDM-1 - Yao, Yancheng; Falgenhauer, Linda; Kempf, Volkhard A. J.; Hogardt, Michael; Göttig, Stephan; Imirzalioglu, Can; Chakraborty, Trinad; Justus Liebig University Giessen (My University, 2017)
The draft genome sequences of two clonal, pandrug-resistant Serratia marcescens clinical isolates were determined. The resistance phenotype was plasmid driven, as 14 of 17 resistance genes were present on large IncFIB(K), IncHI2, and IncA/C2 plasmids indicating a large pool of transmissible antibiotic resistance genes.
Keywords: ddc:610